Dehydration Kinetics of Garlic Slices in Fluidized Bed Dryer - Shoba, S; Champawat, P S; Mudgal, V D; Jain, S K (Journal of Agricultural Engineering, 2013)
Garlic (Allium sativum) slices were dehydrated using fluidized bed dryer at drying air temperature of 40, 50 and60oC and air velocity of 2.5, 3.0 and 3.5m.s-1. Garlic slices dried only in falling rate drying period. Dryingtemperature had significant effect on drying time, whereas air velocity had non-significant effect at 5% level.The effective moisture diffusivity varied from 1.02x10-09 to 1.40x10-09 m2.s-1. Activation energy ranged between12.16 and 12.81kJ.mol-1. The experimental data were fitted to Exponential and Page drying models. Page modelwas found to fit better to describe the drying behaviour of garlic slices.